Selection scheme to increase meat rabbit production: organization system, genetic evaluation and preliminary results - Rosati A.; Fioretti M.; Giovannoli M. (2. International Conference on Rabbit Production in Hot Climates, 1999)
A selection scheme to increase meat rabbit production was organized 1996 by A.I.A. (Italian Animal Breeders Association) and A.N.C.I. (National Rabbit Breeders Association). The organization of selection scheme was planned considering rabbit's particular characteristics (short generation intervals, high prolificy). Basic principles of the scheme were: identification of all animals of the farm and data elaboration directly in the farm. Specific software to collect data and update archives were developed. Data were collected directly by breeders associated to National Rabbit Breeders Association creating a data-set with information of all animals. The genetic evaluation is at the moment carried on a single trait, litter weight at 70 days of age, using a 'BLUP-AM' technology to get an index within farm as the prediction of the additive genetic value for every animal. Progeny of the best indexed individuals are selected to be the next generation's parents, in order to improve both farm's genetic level and phenotypic expression of the considered trait. In the next future a genetic evaluation within farm for other traits (number of animals born alive, number of animals weaned, number of nipples) will be performed using a multiple trait approach for a simultaneous genetic evaluation of all traits. The genetic evaluations for years 1996 and 1997 showed a monthly positive genetic trend of litter weight at 70 days.
2. International Conference on Rabbit Production in Hot Climates, 1998/09/07-09, Adana (Turkey)